Comprehensive Review Discussion of Science Technology Engineering and Mathematics (STEM) Learners in Operations of Integers: An Action Research - Bernal Jr., Hernando L.; Gumaru, Renz Chester R.; Malvas, Kristine Joy R.; Reyes, Jhade J. (RIRAI Publisher, 2024)
Based on perceived general observation, most Senior High School students tend to have difficulties in performing the four basic operations to the set of numbers called “integers”. An integer is a whole number that can be positive, negative, or zero. This study chose Grade 11 Science Technology Engineering and Mathematics (STEM) students as the targeted respondents for this particular action research. It aims to aid STEM students in their struggles on performing operations of integers. The study will use Review Discussion as the intervention and aid for the problem. Results and Interpretation are obtained by using various appropriate statistical formulas like t-test and standard deviation. The researchers conducted this action research to verify if review discussion will have a positive effect and impact on enhancing the skills of Grade 11 STEM students in operations of integers.